Evaluation of All Sexual Abuse Cases and the Child Abuse and Mental Retardation in the Sexual Abuse Cases That Have Been Reflected to Gaziantep University Medicine Faculty Forensic Medicine Department - Isır, Aysun Baransel; Büyükçelik, Ahmet; Özdil, Serdar; Coşkun, Ayşe Gül (The Bulletin of Legal Medicine, 2009)
In sexual abuse several factors are present, we have aimed to take an attention the density and distribution of adult-child and mental retarded sexual abuse victims in this study. 205 sexual abuse cases which have applied to our department between January 2000 and March 2008 have been evaluated by being taken into study scope. 78 of the cases (38%) were male and 127 were female (62%). 103 of the cases were children (50.2%). Youngest of the children were 5 years old and oldest was 18 years old, with the average age of the children calculated as 14.03 + 3.56. 48 of the children cases were male (46.6%) and 55 were female (53.4%). In 42 children (40.8%) post - traumatic stress disorder was detected. The accused of 98 children (95.1%) were strangers. 24 children (23.3 %) who have come to education were illiterate. At 26 of the cases (25.2%), physical violence and compulsion traces were also seen, thus they were concluded to have been exposed to physical abuse as well as sexual abuse. 16 of the children cases (15.5%) were detected to have slight mental retardation. Average age of the mentally retarded children, of which 7 were male (43.8%) and 9 were female (56.2%), was calculated as 16.25+2.543 and the youngest of these was detected as 11 and the oldest was detected as 18 years old. Only at 1 of the mentally retarded children post-traumatic stress disorder was detected. At 6 of the mentally retarded children (37.5 %) physical abuse was detected. All of the mentally retarded children were detected to have been abused by strangers. In sexual abuse several factors are present, among abused children, mentally retarded child cases take an important part and against sexual attacks these cases are more indefensible. In conclusion, the importance and necessity of selective and specific educational programs towards these cases are mentioned as well as medical and social support to them.Key words: Sexual abuse, physical abuse, child, mental retardation
Keywords: sexual abuse; physical abuse; child; mental retardation